APLIKASI MAá¹¢LAHAH MULGAH SEBAGAI METODE ALTERNATIF PENETAPAN HUKUM PROGRESIF - Maimun, Maimun; Muslim, Muslim; Kurniati, Herlina (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2024)
This article examines maá¹£lahah mulgah as an alternative method of establishing progressive law, in resolving contemporary legal cases in Indonesia. The problem is that maá¹£lahah mulgah has so far been underestimated in the ushul fiqh method. The research approach used is qualitative, with a literature study on the application of maslahah mulgah, rules or norms in Islamic law. Meanwhile, the analysis techniques used are qualitative content analysis and holistic interpretation. The results of the discussion show that Maá¹£lahah mulgah can be applied to contemporary legal problems that continue to occur in various aspects by considering the dimensions of the spirit of shari'ah, maqaá¹£id al-syari'ah, maá¹£lahah al-'ammah, and tagayyur al-azminah da al-amkinah, especially on legal problems that fima la naá¹£á¹£a fih, and sukut al-Syari 'an syar'iyyah al-'amal ma'a qiyam al-ma'na al-muqtaá¸a lah. Therefore, one alternative method of progressive ijtihad is maá¹£lahah mulgah